2012
DOI: 10.1016/j.bone.2012.08.128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting versus feeding on the bone metabolic response to running

Abstract: Abbreviations: ACa, albumin-adjusted calcium; Bone ALP, bone alkaline phosphatase; BMD, bone mineral density; P-CTX, C-terminal telopeptide region of collagen type 1; CHO, carbohydrate; FAST, overnight fast from 21:00; FED, a standardised breakfast consumed at 08:15; GLP-1, glucagon-like peptide-1; GLP-2, glucagon-like peptide-2; GIP, glucosedependent insulinotropic polypeptide; LMM, linear mixed model; OC, osteocalcin; OPG, osteoprotegerin; P1NP, N-terminal propeptides of procollagen type 1; PTH, parathyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 62 publications
1
61
2
Order By: Relevance
“…That said, the factors that determine the time course of changes in ß-CTX with endurance exercise remain incompletely understood. For example, ß-CTX increases in the hours after aeute endurance exercise lasting up to 60 min, performed at high exereise intensities including 80% V02max (20), 110% of anaerobic threshold (22), and 115% of ventilatory threshold (VT) (34) but not 85% VT (22), and exereise intensity may be an important factor in this response (22,34,46), It is possible that 65% V02max was not a sufficient intensity to stimulate ß-CTX, With that said, however, we have recently observed a transient increase in ß-CTX after 60 min of running at 65% V02max under identical conditions to those on D5 in SHORT (exercise at 10:30 a.m. in participants fed at 8:00 a.m.) that was no longer evident at 24 h after exercise (47). It is also possible, therefore, that ß-CTX did increase with the exercise bouts, but the response was not sustained through to the following moming.…”
Section: Discussionmentioning
confidence: 72%
“…That said, the factors that determine the time course of changes in ß-CTX with endurance exercise remain incompletely understood. For example, ß-CTX increases in the hours after aeute endurance exercise lasting up to 60 min, performed at high exereise intensities including 80% V02max (20), 110% of anaerobic threshold (22), and 115% of ventilatory threshold (VT) (34) but not 85% VT (22), and exereise intensity may be an important factor in this response (22,34,46), It is possible that 65% V02max was not a sufficient intensity to stimulate ß-CTX, With that said, however, we have recently observed a transient increase in ß-CTX after 60 min of running at 65% V02max under identical conditions to those on D5 in SHORT (exercise at 10:30 a.m. in participants fed at 8:00 a.m.) that was no longer evident at 24 h after exercise (47). It is also possible, therefore, that ß-CTX did increase with the exercise bouts, but the response was not sustained through to the following moming.…”
Section: Discussionmentioning
confidence: 72%
“…Along these lines, another potential limitation is that while all participants performed exercise in the fed condition, we did not record the specific food intake on the day of exercise. Previous research has demonstrated that feeding (vs. fasting) may acutely suppress bone resorption markers (particularly CTx), although bone formation markers, specifically bone ALP, are generally not affected (Clowes et al 2002;Scott et al 2012). In a study examining the effect of feeding on bone markers in women, Clowes et al (2002) demonstrated an 8.5 % decrease in serum NTx in the fed condition.…”
Section: Discussionmentioning
confidence: 90%
“…Six trials determined that glucose was increased in fed conditions following submaximal or prolonged aerobic exercise . The remaining studies indicated glucose was greater in fasted conditions following acute anaerobic or submaximal exercise . Feeding conditions eliciting increases in glucose following exercise compared with fasted conditions included a mixed meal, a glycerol bolus, a carbohydrate‐based meal, an oral carbohydrate solution, and low/high glycaemic index (GI) carbohydrates .…”
Section: Resultsmentioning
confidence: 99%
“…Feeding conditions eliciting increases in glucose following exercise compared with fasted conditions included a mixed meal, a glycerol bolus, a carbohydrate‐based meal, an oral carbohydrate solution, and low/high glycaemic index (GI) carbohydrates . Conversely, feeding interventions which resulted in lower blood glucose compared with fasting included an oral carbohydrate solution, a glucose bolus, and a mixed meal . Gillen et al observed no differences in oral glucose tolerance responses to 6 weeks of fasted vs fed‐state HIIT.…”
Section: Resultsmentioning
confidence: 99%